Рaradigms of programming assembling type in software engeneering - Lavrischeva, E.M. (PROBLEMS IN PROGRAMMING, 2025)
A formal apparatus of paradigms of the programming assembling kind, such as modular, objective, component and service programming is presented: The theoretical apparatus of every paradigm secures the formal development of some program elements of these paradigms, determination of interface these elements in the standard kind and their assembling on the single technological basis in environment of complex of ITC IPS.Prombles in programming 2014; 2-3: 121-132